Evaluation of shear bond strength of composite to newly condensed and set amalgam by using two adhesive systems. (Mustansiria Dental Journal, 2005)
The introduction of adhesives has created a new opportunity to bond compositeresin to existing amalgam restoration on aesthetically disturbing surfaces. Further more ,the composite laminate would probably improve the restoration .This in vitro study was conducted to evaluate the shear bond strength ofcomposite resin to fresh and set amalgam by the use of two adhesive systems and to studythe effect of water storage time on the shear bond strength of composite resin to fresh andset amalgamOne hundred and eighty cylindrical specimens, 5mm high x 5 mm in diameter ,composed of 3 mm of amalgam and 2 mm of composite with a layer of bonding materialin between were prepared. Syntac Sc, Excite, control (non bonding) used to bondcomposite resin (Tetric) to the amalgam bases in three groups I, Il and lll (each onecomposed of 60 amalgam bases). Each group divided into two minor groups each of 30amalgam bases one for fresh amalgam bases referred (F) and the other one for setamalgam bases referred (S), each minor group, F and S subdivided into 3 subgroupsaccording to water immersion period into 48hrs, lmonth, 3months,stored at 37 C forscheduled period of time .